Study of Manufacturing Process of Holes in Aeroengine Heat Shield - Anyuan Jiao; Weijun Liu (International Journal of Aerospace Engineering)
The nickel-based superalloy GH3128 with high plasticity, high long-lasting creep strength, good resistance to oxidation and stamping, and good welding performance is widely used in aircraft engine heat shields. The many holes that need to be machined on the heat shield are not only small in diameter but also dense, and GH3128 as a typical hard-to-process material has the problems of large cutting force, high cutting temperature, and serious hardening. Therefore, poor dimensional accuracy and residual burrs have become the main factors that limit the processing efficiency and processing quality. So, a novel combination of manufacturing processes was proposed. Firstly, laser cutting technology was used to process the base hole in a GH3128 plate, followed by reaming, and finally, using a magnetic abrasive finishing effector to remove burrs formed during the first two steps. The whole drilling process of the heat shields fully meets the requirements of the technical parameters. This study provides new reference for manufacturing the holes of a heat shield and other similar porous parts.